Do organizational culture and work environment affect the motivation and performance of aviation industry employees? - Novitasari, Dewiana; Iskandar, Joni (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this study was to analyze the relationship of organizational culture variables to motivation, organizational culture to performance and the relationship of work environment variables to motivation, work environment to the performance of aviation industry employees. This research method uses quantitative methods through online surveys. The data is obtained through questionnaires distributed online through social media, the respondents of this study were 400 employees of the aviation industry in Banten who were selected through simple random sampling method. Analysis of data processing using Structural Equation Modeling (SEM) with SmartPLS 4.0 software tools. The stages of PLS ​​analysis using smartpls 3 include 3 stages, namely: The outer model testing phase to test the validity & reliability of indicators and constructs, the Goodness of fit model testing phase to test the model's predictive power and model feasibility, The inner model testing phase to test the significance the effect of exogenous variables on endogenous variables.The results of this study are that there is a positive and significant relationship between organizational culture and motivation, there is a positive and significant relationship between organizational culture and performance, there is a positive and significant relationship between work environment and motivation, there is a positive and significant relationship between work environment and performance, and there is a significant relationship between work environment and performance. positive and significant relationship between motivation and performance.